The Monetary and Non-Monetary Aspects of Poverty in Poland and Slovakia - Paweł Ulman (Entrepreneurial Business and Economics Review, 2015)
The purpose of this paper is to present the level of poverty risk of households in Polish and Slovak society in two aspects: monetary and non-monetary. In this study, to evaluate poverty risk in these dimensions, there were used estimated values of the poverty risk function for each household in an integrated, relative and fuzzy approach. This feature has been calibrated to reflect the overall results of the assessment of poverty in the classical approach using relative and subjective methods of determining the poverty line. The research found that there were differences in poverty risk both within national communities and the studied countries. Such two-way diversity of impoverishment was observed primarily in the classification of households due to the demographic composition of the household. There is a need for a broader study of diversity i.a. the structure of poverty, its level, dynamics and factors determining it in both countries. This wide research project may help to answer the question of changes in the evolution of poverty in Slovakia after its accession to the Eurozone, which is extremely important in the context of the Polish accession to the zone. The originality of the work is manifested primarily in a comparative study of poverty risk for communities of the two countries: Poland and Slovakia, which allowed observing differences in the risk in a cross-country system.